EVALUATION ANALYSIS ON A TEXTBOOK ENTITLED âCAMBRIDGE ENGLISH IDIOM IN USE ADVANCEDâ - wijayatiningsih, testiana deni (Fakultas Ilmu Budaya Universitas Jenderal Soedirman, 2018)
This study discussed about an evaluation of textbook analysis entitled âCambridge English Idiom in Used Advancedâ written by written by Felicity OâDell and Michael McCarthy. In this study, the textbook was analyzed using rubric of textbook evaluation in term of layout and design, activities, language type, materials, subject and content. From the discussion, it can be concluded that the book is suitable for advanced learner in term of the composition, given example, exercises and context.